Computed tomography guided fine needle aspiration cytology of thoracic lesions: 10 year experience of an interventional pulmonologist - Saini, Varinder; Garg, Kranti; Handa, Uma; Jaggi, Surabhi; Garg, Ravi Kumar (International Journal of Research in Medical Sciences, 2016)
Background: Diagnosis of thoracic lesions may be challenging, due to various factors associated with the lesion and subsequent invasive investigations. Computed tomography guided fine needle aspiration cytology (CT-guided FNAC) is a minimally invasive method for thoracic lesions considered non approachable by other modalities. Methods: Retrospective analysis of patients subjected to CT-guided FNAC during year 2004 to 2014 was done. In these patients, non-invasive and invasive methods like fibre-optic bronchoscopy/ ultrasound guided FNAC were inconclusive/ expected to be inconclusive. Records were statistically analyzed for patient related, lesion related and procedure related factors, and their effect on yield and complications. Results: 435 patients underwent CT-guided FNAC. Age ranged from 10 to 95 years, with male preponderance. Diagnostic yield was 80.2%. Neoplastic lesions (255/435 (58.6%)) were most commonly diagnosed with majority (206/255 (80.8%)) being non-small cell lung cancer (NSCLC). This was followed by non-neoplastic lesions (94/435 (21.6%)) with Tuberculosis (42/94(44.7%)) being most common in this group. In 227/435 patients, other details like side and size of the lesion, position of patient during the procedure, depth of lesion from skin surface, number of passes undertaken and complications, if any, were also available. They were separately analyzed. Mean size of lesion was 5.7575 X 5.4173cms (maximum vertical X maximum horizontal diameter). Mean depth to which needle was inserted was 5.6663cms. Mean number of passes per patient were 1.98. Right sided lesions were more commonly sampled than left. Supine positioning was most commonly employed. Overall complication rate was 4% (9/227). Conclusions: CT-guided FNAC for thoracic lesions can serve as early diagnostic tool and guide in planning effective management strategies.